Clinical Presentation and Outcome in a Contemporary Cohort of Patients With Acute Myocarditis: Multicenter Lombardy Registry. Issue 11 (11th September 2018) - Ammirati, Enrico; Cipriani, Manlio; Moro, Claudio; Raineri, Claudia; Pini, Daniela; Sormani, Paola; Mantovani, Riccardo; Varrenti, Marisa; Pedrotti, Patrizia; Conca, Cristina; Mafrici, Antonio; Grosu, Aurelia; et al.
Abstract : Background: There is controversy about the outcome of patients with acute myocarditis (AM), and data are lacking on how patients admitted with suspected AM are managed. We report characteristics, in-hospital management, and long-term outcome of patients with AM based on a retrospective multicenter registry from 19 Italian hospitals. Methods: A total of 684 patients with suspected AM and recent onset of symptoms (<30 days) were screened between May 2001 and February 2017. Patients >70 years of age and those >50 years of age without coronary angiography were excluded. The final study population comprised 443 patients (median age, 34 years; 19.4% female) with AM diagnosed by either endomyocardial biopsy or increased troponin plus edema and late gadolinium enhancement at cardiac magnetic resonance. Results: At presentation, 118 patients (26.6%) had left ventricular ejection fraction <50%, sustained ventricular arrhythmias, or a low cardiac output syndrome, whereas 325 (73.4%) had no such complications. Endomyocardial biopsy was performed in 56 of 443 (12.6%), and a baseline cardiac magnetic resonance was performed in 415 of 443 (93.7%). Cardiac mortality plus heart transplantation rates at 1 and 5 years were 3.0% and 4.1%. Cardiac mortality plus heart transplantation rates were 11.3% and 14.7% in patients with complicated presentation and 0% in uncomplicated cases (log-rank P <0.0001). Major AM-related cardiac events after the acute phase (postdischarge death and heart transplantation, sustained ventricular arrhythmias treated with electric shock or ablation, symptomatic heart failure needing device implantation) occurred in 2.8% at the 5-year follow-up, with a higher incidence in patients with complicated forms (10.8% versus 0% in uncomplicated AM; log-rank P <0.0001). β-Adrenoceptor blockers were the most frequently used medications both in complicated (61.9%) and in uncomplicated forms (53.8%; P =0.18). After a median time of 196 days, 200 patients had follow-up cardiac magnetic resonance, and 8 of 55 (14.5%) with complications at presentation had left ventricular ejection fraction <50% compared with 1 of 145 (0.7%) of those with uncomplicated presentation. Conclusions: In this contemporary study, overall serious adverse events after AM were lower than previously reported. However, patients with left ventricular ejection fraction <50%, ventricular arrhythmias, or low cardiac output syndrome at presentation were at higher risk compared with uncomplicated cases that had a benign prognosis and low risk of subsequent left ventricular systolic dysfunction. Abstract : Supplemental Digital Content is available in the text.